2022
DOI: 10.3390/ijms231911937
|View full text |Cite
|
Sign up to set email alerts
|

Caspase 3 and Cleaved Caspase 3 Expression in Tumorogenesis and Its Correlations with Prognosis in Head and Neck Cancer: A Systematic Review and Meta-Analysis

Abstract: Head and neck cancer (HNC) is an ascending and agressive disease. The search for new molecular markers is emerging to solve difficulties in diagnosis, risk management, prognosis and effectiveness of treatments. Proteins related to apoptotic machinery have been identified as potential biomarkers. Caspase 3 is the main effector caspase and has a key role in apoptosis. The objective of this systematic review and meta-analysis is to review studies that analyze changes in Caspase 3 and Cleaved Caspase 3 expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 80 publications
(252 reference statements)
1
5
0
Order By: Relevance
“…The most efficacious dose of Nic-SMEDDS, 100 mg/kg, bid, induced the greatest Ki-67 reduction, suggesting greatest inhibition of tumor cell proliferation ( Figure 3a and b ). Correlating with Ki-67 staining, treatment with all doses of Nic-SMEDDS and NEN increased the levels of activated Caspase-3 protein 29 in PDX tissues, indicating an increased number of activated apoptotic cells; the greatest effect was similarly seen with the most efficacious dose of Nic-SMEDDS at 100 mg/kg, bid ( Figure 3c and d ). We additionally detected cleaved Caspase-3 protein levels in the PDX tissues, harvested at the treatment endpoint.…”
Section: Resultsmentioning
confidence: 79%
“…The most efficacious dose of Nic-SMEDDS, 100 mg/kg, bid, induced the greatest Ki-67 reduction, suggesting greatest inhibition of tumor cell proliferation ( Figure 3a and b ). Correlating with Ki-67 staining, treatment with all doses of Nic-SMEDDS and NEN increased the levels of activated Caspase-3 protein 29 in PDX tissues, indicating an increased number of activated apoptotic cells; the greatest effect was similarly seen with the most efficacious dose of Nic-SMEDDS at 100 mg/kg, bid ( Figure 3c and d ). We additionally detected cleaved Caspase-3 protein levels in the PDX tissues, harvested at the treatment endpoint.…”
Section: Resultsmentioning
confidence: 79%
“…Meanwhile, the influence of Ce6@CQ on tumor cells was further investigated by immunoblotting analysis (Figure B–D). As a vital mediator of apoptosis, Caspase 3 is cleaved at an aspartate in order to produce cleaved caspase 3 (c-Caspase 3), which is accountable for morphological and biochemical changes in apoptosis. , The protein expression of c-Caspase 3 maintained a low level in dark groups, while c-Caspase 3 was significantly activated in light groups. The 4T1 cells treated by Ce6@CQ had the highest expression level of c-Caspase 3 compared to others, suggesting that the apoptotic pathway was triggered intensively.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, caspase-3 is the primary executor of apoptosis, and its activation promotes the degradation of DNA-repairing and cytoskeletal proteins, leading to cell morphological changes and DNA damage, culminating in cell apoptosis (36). Cleaved caspase-3, the active form of caspase-3, is responsible for apoptosis-related morphological and biochemical changes in cells (50). It has been shown that myocardial IR induced significant neuronal apoptosis, as evidenced by an increase in TUNEL-positive cells (31) and upregulation of cleaved caspase-3 expression in brain tissue (30,38).…”
Section: Discussionmentioning
confidence: 99%